Personality Traits and Teaching Practices of Supervisors in Postgraduate Residency Training - Aashi Mughal , Raheela Yasmin , Lubna Meraj, Aashi Mughal , Raheela Yasmin , Lubna Meraj (Journal of Rawalpindi Medical College, 2018)
Background: To study the type of relationship (positive correlation, negative correlation or no correlation) between different traits of supervisor’s personality and their teaching practices in postgraduate residency training. Methods: In this co- relational study registered supervisors (n=121) currently supervising post graduate training and their registered trainees (n=242, two trainees for one supervisor), were included.Two well validated questionnaires namely BFI (Big five inventory) and systematics evaluation of teaching qualities (SETQ) employing five point likert scale were used to collect data. Five factor model (15 items) covering conscientiousness, agreeableness, extraversion, emotional stability and openness was given to assess personality traits of supervisors. Residents evaluated overall teaching practices of respective supervisorusing a validated 21-item System for Evaluation of Teaching Qualities (SETQ) tool. It also evaluated five specific domains like learning climate, professional attitude, communication, evaluation, and feedback. Inter-scale correlations between two scales as a whole and between subscales were calculated by using Pearson’s correlation coefficient (r). Values < 0.05 were taken as statistically significant. Results: Positive correlation(r=.124,p=.175 statistically insignificant) was observed between personality traits and teaching practices. Positive correlation (statistically insignificant) was found between conscientiousness(r =.16, p =.06) and agreeable (r =.06, p =.49) traits of supervisor’s personality with their teaching practices in relation to post graduate training. Conclusion: None of the personality trait of supervisors appeared to have any significant correlation with their teaching performances generally in postgraduate residency training. Positive correlation(statistically significant) was observed between conscientiousness trait of supervisor’s personality and learning climate(r =.18, p =.04), professional attitude (r =.20, p =.02) and feedback (r =.18, p =.04)domains of teaching practices.